Factors for Improving Patient Health Facility Services at the Karang Anyer Health Center Beringin District Deli Serdang Regency - Ambarita, Anna Tirawani; Nainggolan, Fikriyah Arfina (JURNAL KESMAS DAN GIZI (JKG), 2025)
Health is a basic need of every individual which is an important part in improving the quality of human life. The quality of health facility services is one of the main indicators in assessing the success of a country's health care system. Good services not only contribute to improving the health status of the community, but also reflect the effectiveness of the management system and health policy as a whole. Good service quality will have a direct impact on increasing public trust and the effectiveness of patient handling. This study used a quantitative approach with descriptive analytic research. The number of samples determined based on the Slovin formula with a margin of error of 5% amounted to 100 respondents. Based on the results obtained, the variables of officer attitude, availability of medical personnel, and infrastructure have a significant influence on improving service quality (p < 0.05). The variable waiting time has an influence, but is not statistically significant (p> 0.05). Thus, improving service quality at the Karang Anyer Health Center can focus on developing the attitude and competence of officers, equitable distribution of medical personnel, and providing more patient-friendly service facilities.